Development of a new class of diarylpentadienone analogues as anti-diabetic agents - Abdullah, Maryam Aisyah (2019)
Type 2 diabetes mellitus (T2DM) is a chronic disease occurred worldwide and is currently a major cause of morbidity and mortality. Several drugs such as sulfonylureas and biguanides are presently available to reduce hyperglycemia in T2DM patients, however, these medicines possess several side effects and thus searching for a new class of compounds is essential to overcome this problem. Diarylpentadienone is a synthetic compound derived from curcuminoids and chalconoids, which received less extensive studies by researchers, particularly as anti-diabetic agents. In addition, sulfonamide moiety has proven as essential feature for alpha-glucosidase (α-glucosidase) inhibitors and has potential towards dipeptidyl peptidase 4 (DPP-4) inhibitory activity, the two of therapeutic targets for T2DM treatment. In this study, a series of aminated-1,5-diphenylpenta-2,4-dien-1-ones (compounds 1-9) were synthesized by treating aminoacetophenones with differently substituted cinnamaldehydes via Aldol condensation reaction, further completion by sulfonylation reaction with trifluoromethylbenzenesulfonyl chloride to afford the sulfonamide diarylpentadienone analogues (compounds 10-18). The purified intermediate and final compounds were collected and subjected for confirmatory structural elucidation via established spectroscopic techniques comprising of 1H- and 13C- high field nuclear magnetic resonance (NMR), direct injection-mass spectroscopy (DI-MS), and Fouriertransform infrared (FTIR) spectroscopy. These new integrated sulfonamidediarylpentadienone derivatives were screened for their potential anti-diabetic properties through α-glucosidase and DPP-4 in vitro assay. Based on α-glucosidase inhibition results, all sulfonamide-containing analogues (compound 10-18) showed a remarkable suppression activity, in which compound 18 exhibited the highest inhibition with IC50 values of 4.93 ± 0.7 μM, followed by compound 17 (IC50 = 5.83 ± 0.4 μM), in which both analogues demonstrated good inhibitory activity compared to the standard quercetin (IC50 = 6.38 ± 0.4 μM). The structure-activity relationship (SAR) studies revealed that the introduction of the trifluoromethylbenzene sulfonamide on para position of ring A and a lower electron density group (-Cl) on phenyl ring B of diarylpentadienone scaffold enhanced their α-glucosidase inhibition potential. Molecular docking analyses further confirmed the critical role of both sulfonamide and - Cl moieties as they bound to the α-glucosidase active sites, and thus explain their inhibitory activity. Whereas for DPP-4 inhibition activity, none of the synthesized molecules showed a comparable suppression to the standard drug, sitagliptin, (IC50 = 0.07 ± 0.1 μM). However, within the series, compound 15 showed the most active inhibition with IC50 of 25.05 ± 0.38 μM. The SAR studies showed that the introduction of the trifluoromethylbenzene sulfonamide on para position of ring A and methoxy group on para position on ring B seems to exert a positive influence on the DPP-4 inhibition activity of compound 15. The docking analyses between ligand 15 and DPP-4 receptor (PDB ID:5T4B) showed a hydrogen bonding interaction between sulfonamide moiety with amino acid residues (Tyr574) at the hydrophobic site of the enzyme. Overall results suggest that diarylpentadienone with the sulfonamide moiety could be a new selective potential hit molecule in the search of the novel α-glucosidase inhibitors over anti-DPP-4 agents, for the treatments of T2DM patients.